Estudo in situ da deformação criogênica em aços inoxidáveis aisi 430 e AISI 316l utilizando radiação síncrotron - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2018)
Two stainless steels (AISI430 ferritic and AISI316L austenitic) were analyzed by uniaxial tensile tests at room and cryogenic temperatures, with controlled strain rates for both metals. The Gleeble® Synchrotron system was used; it is capable to perform X-ray diffraction measurements in situ, controlling the sample temperature, controlling the stress / strain condition, as well as the chamber atmosphere, and also allowing the injection of liquid nitrogen directly into the sample with excellent versatility and reproducibility. The tests were performed in an advanced thermo mechanical simulation system, XTMS, located in the National Center for Research in Energy and Materials - CNPEM - Campinas, SP, Brazil. The characterization was performed by means of SEM images and in situ XRD. The photomicrographs and the results of the tensile tests show that AISI 430 steel presents a ductile fracture at room temperature and fragile fracture at cryogenic temperature with resistance increasing. The results of the AISI 316 L steel show that the material has a ductile fracture in both conditions. For this same metal, the elongation at both temperatures was practically the same, but the tensile strength in the cryogenic environment was much higher. This behavior may be associated with the TRIP effect, which agrees with the XRD data, since peaks of α’ strain induced martensite are evidenced.
Keywords: Deformação criogênica; Tração uniaxial; Difração de raios X; Temperatura criogênica; Cryogenic deformation; Uniaxial traction; X-ray diffraction; Cryogenic temperature; Mechanical properties; CNPQ::ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA